Medical Informatics Heidelberg/Heilbronn: Graduates’ Experiences and Job Situation - Frey, W.; Haux, R.; Leiner, F.; Leven, F. J. (Methods of Information in Medicine, 1994)
On the occasion of the 20th anniversary of the curriculum of medical informatics at the University of Heidelberg/School of Technology Heilbronn, a written and anonymous inquiry was carried out in March 1992 among the entirety of graduates from the curriculum. The aim of the inquiry was to obtain from the graduates of the curriculum information about their current places of employment, their fields of work, the state of continuing education as well as about their professional position. It was, in addition, intended to obtain from the graduates’ point of view an assessment of the education received during their studies as well as an assessment of the job situation. A questionnaire was sent to all persons having completed their studies by that time (n = 567, as of 1.1.1992). 62.2% of the forms were returned duly filled in; 92.2% of the graduates are employed. 44.5% out of them are working within the field of medical informatics, 53.0% are working outside medical informatics but within the sector of informatics and 2.2% in other fields; 0.3% were without indication. As far as places of employment are concerned, enterprises concentrating on hardware and software development rank first, followed by hospitals and medical institutions affiliated to universities. As far as fields of work are concerned, information systems within the health care sector (especially hospital information systems) as well as medical documentation predominate in the group of those employed within medical informatics, whereas among those not working within medical informatics software engineering as well as database systems and information systems prevail. The judgement passed on the job situation was, in the main, positive. The gross annual income on the average comes to about DM 85,000, every tenth of the graduates draws an income of more than DM 120,000. The assessment of the curriculum on the whole is positive. 68% of the graduates would take up medical informatics again. Twenty-eight of altogether 346 graduates included into the inquiry obtained a doctor’s degree, 2 among them qualified for lecturing in medical informatics.
Keywords: Medical Informatics Education; Medical Informatics Program (University of Heidelberg/School of Technology Heilbronn); Graduates’ Careers